#### Answer

See the picture below.

#### Work Step by Step

The parent function is $f(x)=(\frac{1}{3})^x$ (with red) the given function is $g(x)=(\frac{1}{3})^x+4$ (with blue).
The parent function can be graphed by calculating a few coordinates and connecting them with a smooth curve:
$f(-2)=(\frac{1}{3})^{-2}=9$
$f(-1)=(\frac{1}{3})^{-1}=3$
$f(0)=(\frac{1}{3})^0=1$
$f(1)=(\frac{1}{3})^1=\frac{1}{3}$
$f(2)=(\frac{1}{3})^2=\frac{1}{9}$
For every corresponding x-value the following equation is true: $f(x)+4=g(x)$
This means that the graph is translated 4 units up
($g(x)$ involves a vertical shift of 4).
Every $f(x)$ value will be increased by 4.
(Because the original $f(x)$ will be equal to $f(x)+4$ with the same x-value.
For example if $f(0)=1$ in the original $f(x)$, this will be translated as $f(0)+4=1+4=5$.
We can see that here, the $g(x)$ is greater than $f(x)$ for every corresponding x-value by 4.)